THE EFFECT OF DEPTH SHADING DEVICE ON INNER SPACE ILLUMINATION IN JAKARTA - Panghargiyo, Murwantoro (University Of Technology Yogyakarta, 2019)
This research tries to reveal the performance of shading devices towards quantity of natural lighting entering the room. Investigation concerning shading devices (ratio between the depth of shading devices and the height of fenestration) that suitable with illumination standard needs to be done. This research also tries to find out the influence of shading devices orientation on illuminance received by the room. This research examines the performance of three types external shading devices (eggcrate, overhang, sidefins) towards natural lighting entering the room. The analysis performed by Radiance IES software for illuminance performance entering the room. Maximum illuminance reduction for three types of shading device achieved to north direction in R1 reference point. While minimum reduction for overhang and sidefins achieved to south orientation in R2 reference point. Except for eggcrate minimum illuminance reduction achieved to west direction in R2 reference point. It can be concluded that in general the three basic models of shading device have a strong influence on the direction towards the north and have a small effect on the direction of the south. In addition to the three basic elements of the shading element, the type of eggcrate shading device has the greatest effect of reducing illumination compared to the other two types. While the sidefins type has the smallest illumination effect.